Pengembangan Kemampuan Profesional Petugas Bimbingan dan Konseling di SMU - Deitje A. Katuuk (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
This research was intended to analyze the characteristics and the conceptual framework of the professional development for secondary-school teachers of guidance and counseling. The data were collected from 62 teachers by using questionnaires, attitude scales, and ability test. The results of frequency percentages show that teachers’ professionalism varied, particularly in terms of their subject mastery, profession, and practical experience. Additionally, they had positive attitudes toward guindance and counseling. Unfortunately, the facilities to carry out guidance and counseling services were not adequate. It was then suggested that teachers of guidance and counseling be provided with continuous training.